Udział polskich uczonych poza granicami kraju w tworzeniu kierunków sowietologii po drugiej wojnie światowej - Bosiacki, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
The article presents the participation of Polish scholars in the research on Russia and on the Union of Soviet Socialist Republic after World War II, which was conducted in scientific centers of Europe and the United States. Describing the participation of Poles and of people of Polish descent, the author comes to the conclusion that the scholarly interest in Russia both in Poland and among Polish emigrants dates at least for several generations and concerns many fields of scientific endeavor. In particular, the article pinpoints and describes the conceptions of such scholars as Jan Kucharzewski and Richard Pipes historiography, Adam Ulam, Leopold Łabędź and Zbigniew Brzeziński political science, with special emphasis placed upon a theory of international relations, Father Innocenty Bocheński, Leszek Kołakowski and Andrzej Walicki history of ideas and philosophy, and even economic science Stanislaw Swianiewicz. As the author contends, both disciplinarily and substantively, their efforts mark a very important contribution, constituting significant achievements of Polish science, notwithstanding the fact that many scholars have declared and still declare only possessing Polish origins, often considering themselves to be Americans. The subject of the article is also a field for further scholarly research which is worth exploring and which the author intends to undertake.
Keywords: polscy uczeni; sowietologia; Związek Radziecki